A Simple Model of Bank Behaviour—With Implications for Solvency Regulation. (June 2015) - Zweifel, Peter; Pfaff, Dieter; Kühn, Jochen
A simple model of bank behaviour is shown to have implications for solvency regulation of the Basel type. The investment division seeks to maximize RORAC, with higher solvency S lowering the cost of refinancing but tying costly capital. In period 1, exogenous changes in expected returns d μ ¯ and in volatility d σ ¯ occur, causing optimal adjustments dS */ d μ ¯ and dS */ d σ ¯ in period 2. In period 3, the actual adjustment dS * creates an endogenous trade-off with slope d μ ^ / dσ ^ . Basel- type regulation modifies this slope, inducing senior management to opt for a higher value of σ in several situations. Solvency regulation can thus run counter its stated objective.